ANALISIS PENENTUAN HARGA POKOK PRODUKSI DENGAN METODE FULL COSTING DAN VARIABLE COSTING SEBAGAI DASAR PENENTUAN HARGA JUAL - Misnawati (FEB Universitas Lakidende, 2020)
This research was conducted to determine the calculation of the cost of goods manufactured and the selling price according to the company, the full costing method and the variable costing method. The results of this study indicate that there are differences in the results of the calculation of the cost of goods manufactured and the selling price carried out between the company method with the full costing method and the variable costing method. The calculation using the company method yields a production cost of Rp. 3,231,000 with a selling price of Rp. 4,000,000, while according to the full costing method the cost of production is Rp. 3,571,551 with a selling price of Rp. 4,535,869 and according to the variable costing method The cost of production is Rp. 3,225,384 with a selling price of Rp. 4,096,238. The difference is because the calculations made by the company have not recognized all costs related to the production process. This study concludes that the calculation of the cost of production and the selling price by the company is not right, because it does not enter costs properly